Biomechanics of squat jump in junior badminton players - Vora, M.; Ranawat, D.; Arora, M.; Tiwari, A. (ARC Journal of Research in Sports Medicine, 2019)
In badminton, the overhead jump smash is one of the most commonly used strokes. One of the key components of the smash is the ability to squat jump well before striking the shuttlecock. Improvement in squat jump could help improve the badminton overhead smash and overall improvement in performance. Accordingly, the study was proposed to analyse the biomechanics of squat jump in junior badminton players and understand its importance. A total of 100 players from South Asia between the ages of 8 and 15 years were analysed. Iso Lift system of Tecnobody Italy was used. Variables measured were gender, height, age, body mass index, and experience in years, level at which theyplay, current pain, and clicks & catches in the past 1 year. Our study showed that there was significant difference in maximum force of squat jump in terms of body mass index and in maximum relative power of squat jump in terms of level at which players compete. There are a variety of other factors which do not affect squat jump. There needs to be a greater focus on squat jump training with a specialised strength and conditioning coach as part of the development of junior badminton players.